Pengaruh Formulasi Serum Nanoemulgel Terhadap Aktivitas Antioksidan Ekstrak Daun Kelor - Ramadhani, Diah; Widiyanti , Nabilla (CV RIFAINSTITUT, 2022)
Moringa leaves (Moringa oleifera L.) are a good source of natural antioxidants because they contain flavonoids. The purpose of this study was to determine whether Moringa leaf extract can be formulated into nanoemulgel serum preparations, and to see the effect of nanoemulgel serum formulations on antioxidant activity. This research begins with the manufacture of extracts using the maceration method, followed by the manufacture of nanoemulsions. The nanoemulsion consisted of 3 formulations with different Moringa leaf extract, namely the formulation of 1 0.1 g, formulation 2 0.2 g, and formulation 3 0.4 g of Moringa leaf extract were given. The nanoemulsion was tested for particle size distribution using a Particle Size Analyzer and tested for the physical stability of the preparation. The results showed that the nanoemulsion particle size in formulation 3 had a smaller distribution size of 13.7 nm and was continued for the manufacture of serum nanoemulgel. Serum nanoemulgel consists of 4 formulations with variations of nanoemulsion. The nanoemulgel serum formulation was tested for its physical stability and antioxidant activity using the DPPH method. The antioxidant activity of the nanoemulgel serum preparations had IC50 of each formulation 1 70.5197 ppm, formulation 2 62.7838 ppm, and formulation 3 50.6094 ppm. The nanoemulgel serum formulation which has the highest antioxidant activity is formulation 3